2016
DOI: 10.1016/j.bandl.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Lexical selection differences between monolingual and bilingual listeners

Abstract: Three studies are reported investigating how monolinguals and bilinguals resolve within-language competition when listening to isolated words. Participants saw two pictures that were semantically-related, phonologically-related, or unrelated and heard a word naming one of them while event-related potentials were recorded. In Studies 1 and 2, the pictures and auditory cue were presented simultaneously and the related conditions produced interference for both groups. Monolinguals showed reduced N400s to the sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
2
12
0
4
Order By: Relevance
“…Comparable results were reported by Stein et al (Stein, Federspiel, Koenig, Wirth, Lehmann, Wiest, Strik, Brandeis & Dierks, 2009). Differences related to proficiency in the activation of left prefrontal areas might also reflect the increased role played by the brain's executive network in solving cognitive conflicts caused by the challenging mixed context (Braver et al, 2001; Carter & van Veen, 2007; Wang et al, 2007; Friesen, Chung-Fat-Yim & Bialystok, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were reported by Stein et al (Stein, Federspiel, Koenig, Wirth, Lehmann, Wiest, Strik, Brandeis & Dierks, 2009). Differences related to proficiency in the activation of left prefrontal areas might also reflect the increased role played by the brain's executive network in solving cognitive conflicts caused by the challenging mixed context (Braver et al, 2001; Carter & van Veen, 2007; Wang et al, 2007; Friesen, Chung-Fat-Yim & Bialystok, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This convergence undoubtedly facilitates the correct selection most of the time, but it also leads to selection errors, so it is part of the constellation of factors that determine lexical selection by bilinguals. Monolinguals also need to select between competing alternatives, but the conditions under which those selections are made, the processes underlying the selection, and the electrophysiological correlates of those selections are different for monolinguals and bilinguals (Friesen, Chung-Fat-Yim, & Bialystok, 2016). Experiencing multiple cultures is unique to bilinguals, so understanding the role of cultural context in lexical selection will provide a more complete account of language processing in bilinguals.…”
mentioning
confidence: 99%
“…Similarly, it may be that bilinguals demonstrate a greater reliance on phonological information than semantic information. However, we consider this explanation unlikely as most prior research with bilinguals has shown reduced lexical activation compared with monolinguals, at least as assessed with several different language tasks (Friesen et al, 2016;Gollan & Silverberg, 2001; see Bialystok, 2017, for review). Within the context of current theories of DRM false memories, one possible explanation for the increased level of phonological false memories in bilinguals is that they are more reliant on gist representations than are monolinguals.…”
Section: Attentional Control Mechanisms In Monolingual and Bilingual Language Processingmentioning
confidence: 92%
“…One consequence of jointly activated languages is that lexical access is more difficult for bilinguals than for monolinguals, as is shown by performance in picture naming (Friesen, Chung-Fat-Yim, & Bialystok, 2016;Gollan, Montoya, Fennema-Notestine, & Morris, 2005;Sullivan, Poarch, & Bialystok, 2018), tip-of-the tongue events (Gollan & Silverberg, 2001), and verbal fluency tasks (Giezen & Emmorey, 2017;Gollan, Montoya, & Werner, 2002;Luo, Luk, & Bialystok, 2010). Yet, despite both languages being constantly active, bilinguals rarely make language intrusion errors (Gollan, Sandoval, & Salmon, 2011;Myers-Scotton, 2002;Sandoval, Gollan, Ferreira, & Salmon, 2010).…”
mentioning
confidence: 99%